Prenatal Diagnosis and Findings in Ureteropelvic Junction Type Hydronephrosis - Has, Recep; Sarac Sivrikoz, Tugba (Frontiers in Pediatrics, 2020)
The widespread use of obstetric ultrasonography has increased the detection rate of antenatal hydronephrosis. Although most cases of antenatal hydronephrosis are transient, one third persists and becomes clinically important. Ultrasound has made differential diagnosis possible to some extent. Ureteropelvic junction type hydronephrosis (UPJHN) is one of the most common cause of persistent fetal hydronephrosis and occurs three times more in male fetuses. It is usually sporadic and unilateral. However, when bilateral kidneys are involved and presents with severe hydronephrosis, the prognosis may be poor. Typical ultrasound findings of UPJHN is hydronephrosis without hydroureter. The size and appearance of the fetal bladder is usually normal without thickening of the bladder wall. Several grading systems are developed and increasingly being used to define the severity of prenatal hydronephrosis and provides much more information about prediction of postnatal renal prognosis. If fetal urinary tract dilation is detected; laterality, severity of hydronephrosis, echogenicity of the kidneys, presence of ureter dilation should be assessed. Bladder volume and emptying, sex of the fetus, amniotic fluid volume and presence of associated malformations should be evaluated. Particularly the ultrasonographic signs of renal dysplasia, such as increased renal parenchymal echogenicity, thinning of the renal cortex, the presence of cortical cysts, and co-existing oligohydramnios should be noticed. Unfortunately, there is no reliable predictor of renal function in UPJHN cases. Unilateral hydronephrosis cases suggesting UPJHN are mostly followed up conservatively. However, the cases with bilateral involvement are still difficult to manage. Timing of delivery is also controversial.